Loss of hexokinase 1 sensitizes ovarian cancer to high-dose metformin - Šimčíková, Daniela; Gardáš, Dominik; Hložková, Kateřina; Hruda, Martin; Žáček, Petr; Rob, Lukáš; Heneberg, Petr (Cancer & metabolism, 2021)
BACKGROUND: Hexokinases (HKs) are well-studied enzymes catalyzing the first step of glycolysis. However, non-canonical regulatory roles of HKs are still incompletely understood. Here, we hypothesized that HKs comprise one of the missing links between high-dose metformin and the inhibition of the respiratory chain in cancer. METHODS: We tested the isoenzyme-specific regulatory roles of HKs in ovarian cancer cells by examining the effects of the deletions of HK1 and HK2 in TOV-112D ovarian adenocarcinoma cells. We reverted these effects by re-introducing wild-type HK1 and HK2, and we compared the HK1 revertant with the knock-in of catalytically dead HK1 p.D656A. We subjected these cells to a battery of metabolic and proliferation assays and targeted GC×GC-MS metabolomics. RESULTS: We found that the HK1 depletion (but not the HK2 depletion) sensitized ovarian cancer cells to high-dose metformin during glucose starvation. We confirmed that this newly uncovered role of HK1 is glycolysis-independent by the introduction of the catalytically dead HK1. The expression of catalytically dead HK1 stimulated similar changes in levels of TCA intermediates, aspartate and cysteine, and in glutamate as were induced by the HK2 deletion. In contrast, HK1 deletion increased the levels of branched amino acids; this effect was completely eliminated by the expression of catalytically dead HK1. Furthermore, HK1 revertants but not HK2 revertants caused a strong increase of NADPH/NADP ratios independently on the presence of glucose or metformin. The HK1 deletion (but not HK2 deletion) suppressed the growth of xenotransplanted ovarian cancer cells and nearly abolished the tumor growth when the mice were fed the glucose-free diet. CONCLUSIONS: We provided the evidence that HK1 is involved in the so far unknown glycolysis-independent HK1-metformin axis and influences metabolism even in glucose-free conditions.